Fisuras de contracción en pavimentos de hormigón y el aserrado de juntas - Barreda, M. F.; Naber, M. J.; Quispe Sallo, I.; Sota, J. D. (Revista ALCONPAT, 2013)
In the hardened concrete of pavements, with limited deformation, volumetric changes due to variations in temperature and humidity cause tensile stresses, with subsequent cracks random. The presence of shrinkage cracks in concrete pavements, reduces its service life and generates substantial maintenance costs. It is necessary to define a priori the location of cracks, by sawing the pavement. Sawn areas create planes of weakness where cracks form, being critical the right time to saw the contraction joints in pavements. The optimal time to perform the sawing is called sawing window. In this paper the first results about concrete pavements are recorded, establishing sawing times, comparing cylindrical compressive strength, maturity of concrete and ultrasonic pulse values. The studies are part of a R & D project.